EURO-INTEGRATION POTENTIAL OF PUBLIC ASSOCIATIONS IN UKRAINE - Зерницький, Р. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The transformation of political culture and the formation of the European self-consciousness of Ukrainians as key elements of the successful integration of Ukraine with the European Union are observed in the article. The activity of seven all-Ukrainian public associations working in the vector of Euro-integration are analyzed. The level of influence of public associations on these processes is assessed. It was found out that the actual political influence of public associations in Ukraine is unsatisfactory and insufficient to achieve their global goals.